2006
DOI: 10.1177/1090198106288596
|View full text |Cite
|
Sign up to set email alerts
|

Educational Web-Based Intervention for High School Students to Increase Knowledge and Promote Positive Attitudes Toward Organ Donation

Abstract: A sample of 490 high school students from 81 schools in Michigan participated in an experiment in which they were randomly assigned to either a control or an experimental Web site. The experimental Web site provided exposure to educational material about the process of organ donation and organ transplantation. The control Web site provided educational material on methods to avoid the common cold. The pre-and posttests of knowledge of issues related to organ donation and of attitude toward donation demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 15 publications
1
30
0
2
Order By: Relevance
“…Using the internet to provide health information has many advantages, including convenience and anonymity for those who want information but are not comfortable consulting with a healthcare provider (Hanauer, Dibble, Fortin, & Col, 2004). In previous research on college students, web-based interventions have been shown to alter attitudes toward organ donation (Vinokur, Merion, Couper, Jones, & Dong, 2006) and problem drinking (Kypri et al, 2004). Key issues related to the use of the internet for web-based health interventions include accessibility and the utility of the particular website (e.g., how easy it is to navigate the website and understand the information presented) (O'Grady, 2006;Taylor, Jobson, Winzelberg, & Abascal, 2002).…”
mentioning
confidence: 98%
“…Using the internet to provide health information has many advantages, including convenience and anonymity for those who want information but are not comfortable consulting with a healthcare provider (Hanauer, Dibble, Fortin, & Col, 2004). In previous research on college students, web-based interventions have been shown to alter attitudes toward organ donation (Vinokur, Merion, Couper, Jones, & Dong, 2006) and problem drinking (Kypri et al, 2004). Key issues related to the use of the internet for web-based health interventions include accessibility and the utility of the particular website (e.g., how easy it is to navigate the website and understand the information presented) (O'Grady, 2006;Taylor, Jobson, Winzelberg, & Abascal, 2002).…”
mentioning
confidence: 98%
“…Tier three focused on reaching people without access in public libraries. OneLegacy partnered with libraries throughout the state to help people who may not have computers at home access the online registry 13. Siminoff et al1 identified the strongest predictor of refusal to donate to be the belief that the deceased would have not wanted to donate.…”
Section: Discussionmentioning
confidence: 99%
“…Birincisi gençlerde organ bagi §i ve nakline kar §i olumlu bir tutum olu §turmak ya da olumsuz tutumu degiçtirmek yeti §kin insanlardan daha kolaydir. Ikincisi gençler nüfusun büyük bir bölümünü olu §turmalarinm yani sira nakil için uygun organlari sagiayan ölümcül yaralanmalara yüksek oranda ugramaktadirlar (18). Bu sebeple toplumsal farkindahgin arttirilmasindaki en iyi yol gençlerin bu konuda bilgilendirilmeleridir.…”
Section: Tablo 4 öGrencilerin Bilgilendirme öNcesinde Ve Sonrasinda unclassified
“…Özdag, Ingiltere ve Ispanya'nin organ bagifi konusunda önde gelen ülkelerin baçinda geldigi ve bu ülkelerde organ bagiçina ilifkin egitimin ilkokuldan baflandigmi belirtmiçtir (3). Bizim çali|mamiz ve yapilan birçok çali §ma egitim programlarmin ögrencilerin organ bagi §i ve nakli hakkindaki bilgi düzeyini arttirdigini ve olumlu tutumlar geli §tirdigini göstermektedir (5,6,(18)(19)(20)(21)(22). Yine bu çaliçmada bilgilendirme öncesinde organ bagi §i ve naklini onaylayanlarin orani %64,7 iken bilgilendirme sonrasmda bu oran %80,9'a yükselmi §tir.…”
Section: Tablo 4 öGrencilerin Bilgilendirme öNcesinde Ve Sonrasinda unclassified